Less Social Health Insurance – More Private Supplementary Insurance? – Empirical Evidence from Germany - Boris Augurzky; Harald Tauchmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper uses individual level data to analyze the effect of changes in the compulsory benefit package of the German statutory health insurance scheme on the demand for private supplementary insurance. In particular, we aim at measuring the effect of excluding dentures from the benefit package in 1997 as well as the effect of re-including them in 1999. A difference-in-differences estimator is used. Individuals born prior to 1979 serve as control group because only the young were affected by the reform. Our results do not exhibit any significant effects on the demand for supplementary health insurance. Thus, the hypothesis that clients do make informed choices about their health insurances' coverage is not supported.
Keywords: I12; P23; 330; Supplementary private health insurance; dentures; difference- in-differences; Gesetzliche Krankenversicherung; Gesundheitsreform; Dentalprodukt; Private Krankenversicherung; Konsumentenverhalten; Deutschland